Analisis Pengelolaan Anggaran Pendapatan Dan Belanja Desa (APBDes) Didesa Gaya Jaya Kecamatan Lawe Sigala-Gala - Rifka Sepliana Marpaung; Herti Diana Hutapea; Ardin Dolok Saribu (Jurnal Minfo Polgan, 2024)
This study aims to determine the process of planning, implementing, administering, reporting and accountability of the Village Revenue and Expenditure Budget in Gaya jaya Village, Lawe sigala-gala District in accordance with the Regulation of the Minister of Home Affairs Numbers 20 of 2018 concerning village financial management. This study is a type of qualitative descriptive research using primary data and secondary data, where primay data is in the form of direct observation result in the form of interviews regarding the planning, implementation, administration, reporting and accountability of the Village Budget of Gaya jaya Village, Lawe sigala-gala District in 2023 while secondary data uses the financial report of the Village Budget of Gaya jaya Village, Lawe sigala-gala District. In this study, data analysis techniques were used by means of data consistency and data presentation and drawing conclusions. The result of this study indicate that the management of the Village Budget of Gaya jaya Village, Lawe sigala-gala District, including planning, implementation, reporting, and accountability, has been carried out in accordance with the Regulation of the Minister of Home Affairs Number 20 of 2018. However, the administration section is not in accordance with the Regulation of the Minister of Home Affairs Number 20 of 2018, so in this case it must remain or be given guidance and direction from the Gaya jaya Village government.